Photocatalytic Oxidation of Acetone Over High Thermally Stable TiO2 Nanosheets With Exposed (001) Facets - Shi, Ting; Duan, Youyu; Lv, Kangle; Hu, Zhao; Li, Qin; Li, Mei; Li, Xiaofang (Frontiers in Chemistry, 2018)
Anatase TiO2 (A-TiO2) usually exhibits superior photocatalytic activity than rutile TiO2 (R-TiO2). However, the phase transformation from A-TiO2 to R-TiO2 will inevitably happens when the calcination temperature is up to 600°C, which hampers the practical applications of TiO2 photocatalysis in hyperthermal situations. In this paper, high energy faceted TiO2 nanosheets (TiO2-NSs) with super thermal stability was prepared by calcination of TiOF2 cubes. With increase in the calcination temperature from 300 to 600°C, TiOF2 transforms into TiO2 hollow nanoboxes (TiO2-HNBs) assembly from TiO2-NSs via Ostwald Rippening process. Almost all of the TiO2-HNBs are disassembled into discrete TiO2-NSs when calcination temperature is higher than 700°C. Phase transformation from A-TiO2 to R-TiO2 begins at 1000°C. Only when the calcination temperature is higher than 1200°C can all the TiO2-NSs transforms into R-TiO2. The 500°C-calcined sample (T500) exhibits the highest photoreactivity toward acetone oxidation possibly because of the production of high energy TiO2-NSs with exposed high energy (001) facets and the surface adsorbed fluorine. Surface oxygen vacancy, due to the heat-induced removal of surface adsorbed fluoride ions, is responsible for the high thermal stability of TiO2-NSs which are prepared by calcination of TiOF2 cubes.